Diálogos possíveis com Clarice Lispector": As entrevistas de uma escritora jornalista - Rossi, Vera Helena Saad (2006)
This research purposes to analyze the language built in the Clarice Lispector interviews accomplished to Manchete e Fatos e Fotos/Gente magazines, in order to investigate possible opportunities of fiction inside the journalistic texts, and, thereby, to evaluate the singularity of this interviews. Therefor, we studied theoretical concepts about the interview genre and the journalistic language. We also pointed out the main differences between journalistic speech and literary speech before analyzing the Clarice Lispector interviews. Due to the fact that the Clarice Lispector profession as a journalist is not too much known, we trace the press trajectory of the writer, based on the Aparecida Maria Nunes research, and the course which leads Clarice to Bloch Editores. Fifteen interviews from Manchete and sixteen from Fatos e Fotos/Gente were selected. Since these texts are from magazines, there is a concerning in studying the interviewer and interviewed voices in a contextual time and space. By the analytic lecture of the interviews, we emphasized the peculiar clarician language, that, usually, dialogues with the Clarice Lispector literature work